2021
DOI: 10.18178/ijiet.2021.11.11.1561
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy for Self-regulated Learning and Chinese Students’ Intention to Use Online Learning in COVID-19: A Moderated Mediation Model

Abstract: Self-efficacy for self-regulated learning (SESRL) is a protective factor for academic performance. However, there are few studies have explored its impact on online learning during the Covid-19. This study investigated (a) the mediating roles of perceived usefulness (PU) and perceived ease of use (PEOU) in the relationship between SESRL and use intention (UI) and (b) the moderating role of gender in the indirect relationship between SESRL and UI. Four hundred Chinese college students entered this study and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This theory is based on the theory of reasoned action (TRA) and involves the perspective of social cognitive and behavioral decisions (Qu and Chen, 2021). Cui (2021) confirmed that the TAM is very useful to explain for the variance of the acceptance and usage in technological systems. It believes that when users access a new system, many factors influence their decisions about how and when they use it (Davis, 1989).…”
Section: Dandm Is Success Modelmentioning
confidence: 89%
See 3 more Smart Citations
“…This theory is based on the theory of reasoned action (TRA) and involves the perspective of social cognitive and behavioral decisions (Qu and Chen, 2021). Cui (2021) confirmed that the TAM is very useful to explain for the variance of the acceptance and usage in technological systems. It believes that when users access a new system, many factors influence their decisions about how and when they use it (Davis, 1989).…”
Section: Dandm Is Success Modelmentioning
confidence: 89%
“…In contextual features of online learning environment, similarly, many scholars have successfully carried out with the TAM to predict behavioral intention to use and use of OLSs through various major factors, such as perceived usefulness, perceived ease of use, selfefficacy, subjective norm, enjoyment, computer anxiety and prior experience (Al-Fraihat et al, 2020;Cui, 2021;Abdullah and Ward, 2016;Sahin and Shelley, 2008). According to Sumak et al (2011), the TAM is the most common ground theory employed in e-learning acceptance study with 86% of research using this model.…”
Section: Dandm Is Success Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, factors affecting learner satisfaction should be considered in online learning [7]. If learners recognize the benefits and the ease of using an e-system, they will be enabled to learn independently [8]. Moreover, instructors must answer questions quickly and provide timely feedback and suggestions regarding assigned tasks.…”
Section: Introductionmentioning
confidence: 99%